1999
DOI: 10.1002/(sici)1097-461x(1999)72:4<295::aid-qua12>3.3.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Interconversions of Z‐1,3,5‐hexatriene conformers: A theoretical study

Abstract: ABSTRACT:A two-dimensional potential-energy surface was calculated for the ground state of Z-1,3,5-hexatriene in order to study the conformational relaxation after its photochemical formation from 1,3-cyclohexadiene. The potential-energy surface was scanned along both C-C single bond torsional angles while all other internal coordinates were optimized at the DFTrB3LYPr6-31G UU level. The three conformational minima corresponding to cZc-, tZc-, and tZt-hexatriene as well as four transition states were localized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 0 publications
3
11
0
Order By: Relevance
“…For the energy differences between the conformers and for the barrier heights, we took the ab initio values of Pullen et al (Table ). They well agree with previous calculations. , Slightly higher values were found in very recent density-functional calculations 1 Energies of the Less Stable Conformers and Transition States (TS) (see Figure ) Relative to the Ground State of tZt- Hexatriene as Calculated by Pullen et al The Barrier Heights Are Not far from Those in Butadiene 48 and Octatetraene 49 cZc -HTTS between cZc and cZt cZt -HTTS between cZt and tZt tZt -HT energy/cm -1 2956 3370 1088 1809 0 …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…For the energy differences between the conformers and for the barrier heights, we took the ab initio values of Pullen et al (Table ). They well agree with previous calculations. , Slightly higher values were found in very recent density-functional calculations 1 Energies of the Less Stable Conformers and Transition States (TS) (see Figure ) Relative to the Ground State of tZt- Hexatriene as Calculated by Pullen et al The Barrier Heights Are Not far from Those in Butadiene 48 and Octatetraene 49 cZc -HTTS between cZc and cZt cZt -HTTS between cZt and tZt tZt -HT energy/cm -1 2956 3370 1088 1809 0 …”
Section: Resultssupporting
confidence: 90%
“…17 This is consistent with the 15 ps time constant for cZt f tZt predicted on the bases of two-dimensional surfaces calculated by density-functional theory. 47 Recent time-resolved investigations by means of IR spectroscopy only found an upper bound for this time: It showed that Z-hexatriene produced by the ring opening of 1,3-cyclohexadiene isomerizes completely to the tZt conformer in less than 20 ns. 58 In the case of exciting tZt-hexatriene, the high temperature of the molecules after the internal conversion leads to an increase of the concentrations of the high-energy conformers during the first 2.5 ps.…”
Section: Ts Between Czt and Tzt Tzt-ht Energy/cmmentioning
confidence: 99%
“…Previous studies confirm our distributions; the ∅ 1 / ∅ 3 -map of HT (Fig. 2) is similar to the map reported by Henseler et al 54 and the dihedral angle conformations of some minimum energy structures of 2,5-IMHT previously determined by DFT 25 are consistent with the high-density regions in Fig. 3 C.…”
Section: Resultssupporting
confidence: 91%
“…The ring-opening reaction of 1,3-cyclohexadiene (CHD) and subsequent relaxation of hot 1,3,5- cis -hexatriene (Z-HT) provides an interesting paradigm for the detailed investigation of energy flow in a chemical system. Several groups have investigated both the electrocyclic ring-opening reaction of CHD, and of the related 7-dehydrocholesterol chromophore responsible for the photoreaction that results in vitamin D formation. Initial UV excitation of CHD produces a population in the 1 1 B state which decays by internal conversion to an optically forbidden 2 1 A state on a time scale of ca. 10 fs. , The electrocyclic ring-opening reaction of CHD occurs on the 2 1 A state and produces vibrationally hot cis -1,3,5-hexatriene with a quantum yield of 0.40 .…”
Section: Introductionmentioning
confidence: 99%
“…The transition states for cZt f tZt (TS2) and cZc f cZt (TS1) are indicated on the plot, as are approximate reaction coordinates (green dashed line). A more complete energy surface is provided by Hensler et al22…”
mentioning
confidence: 99%